Liraglutide: from clinical trials to clinical practice. - Gough, S (2012)
Liraglutide, a once-daily glucagon-like peptide-1 receptor agonist, is approved for use as monotherapy in the USA and Japan (but not in Europe or Canada) and in combination with selected oral agents (all regions) for the treatment of patients with type 2 diabetes. Guidance from local advisory bodies is emerging on the most appropriate place for liraglutide in the treatment pathway. It is apparent from its phase 3 clinical trial programme that liraglutide provides superior glycaemic control compared with that achieved with other antidiabetic agents used early in the treatment pathway (e.g. glimepiride and sitagliptin). Key additional benefits include a low incidence of hypoglycaemia and clinically relevant weight loss, although these benefits may be ameliorated by concomitant sulphonylurea (SU) treatment and, in the case of hypoglycaemia, reduction of the SU dose may be necessary. Overall, the profile of liraglutide is similar and, in some aspects, superior to twice-daily exenatide. The implementation of liraglutide therapy is straightforward, with simple dose titration from the starting dose of 0.6 to 1.2 mg/day after 1 week; some patients may benefit from additional titration to 1.8 mg/day. Treatment is self-administered by subcutaneous injection. This contrasts with other agents used early in the treatment pathway, but clinical data suggest patients' overall treatment satisfaction with liraglutide is similar (1.2 mg) or better (1.8 mg) than that with sitagliptin despite differing administration methods. Some patients may experience nausea when initiating liraglutide treatment, but the titration regimen is designed to improve tolerability and clinical data indicate nausea is transient.